Validity and reliability of the lode excalibur sport cycle ergometer for the wingate anaerobic test - Lunn, William R.; Axtell, Robert S. (The Journal of Strength & Conditioning Research, 2019)
Lunn, WR and Axtell, RS. Validity and reliability of the Lode Excalibur Sport cycle ergometer for the Wingate Anaerobic Test. J Strength Cond Res XX(X): 000–000, 2019—Although multiple testing devices advertise Wingate Anaerobic Test (WAnT), capability, reliability, and validity data are sparse. The purpose was to determine whether the Lode Excalibur Sport cycle ergometer is a reliable and valid instrument to conduct the 30-second WAnT when compared with the Monark 894e Peak Bike ergometer. Recreationally active men (n = 49; 20.6 ± 2.5 years; 1.75 ± 0.07 m; and 79.1 ± 9.8 kg) completed four 30-second WAnTs: 2 each on the Lode and the Monark ergometers for peak power (PP), mean power (MP), minimum power (MinP), fatigue index (FI), and peak cadence (vmax) measurement. Interday and interunit correlation, multivariate analysis of variance, regression, and Bland-Altman analysis determined reliability and validity. Cohen's d was used to determine effect size. Relative reliability (intraclass correlation coefficient) with 95% confidence interval for Monark and Lode was very high for PP, MP, MinP, and vmax and high for FI (r > 0.83; coefficient of variation ≤ 27.0%; p < 0.01). Interunit correlation was strong for PP, MP, MinP, and vmax (r > 0.75; p < 0.001) and moderate for FI (p = 0.001). Lode PP and FI values were significantly less (p < 0.001; d > 1.18) and MinP, MP, and vmax significantly greater (p ≤ 0.001; d > 0.51) than Monark. Proportional bias was demonstrated for all variables (p < 0.04; d > 2.68) except vmax. The Lode ergometer reliably provides WAnT outcomes and correlates well to the Monark ergometer. However, differences in power values and proportional bias between differently braked instruments prevent use of the Lode ergometer for comparison of WAnT data with normative data generated by the Monark ergometer.
Keywords: dept.hms; peer-reviewed